2023
DOI: 10.1007/s11367-023-02135-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of transhumant sheep farms: accounting for natural baseline emissions in Mediterranean systems

Abstract: Purpose Transhumance has rarely been analyzed through LCA approaches, and there is little evidence about its emissions level when conducted under different practices (by truck or on foot) or compared to sedentary livestock systems. Moreover, mobile pastoralism is strongly linked to natural resources by its seasonal grazing patterns, thereby occupying the niche of wild herbivores. Considering natural emission baselines in these ecosystems could have relevant effects when estimating their carbon fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Designing compensation regimes for the ecosystem services provided by pastoral systems could be a tool to improve the competitiveness of these systems [ 46 ], which are otherwise at a disadvantage compared to permanently establishing intensive systems, both from an economic and productive point of view [ 47 ]. Areas with low cropping potential (e.g., arid or mountainous areas), such as the farms studied, depend on grazing [ 14 , 17 ]. While vegetation plays a critical role in mitigating climate change, it also plays an important role in supporting global biodiversity and providing many goods and services to humans [ 9 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Designing compensation regimes for the ecosystem services provided by pastoral systems could be a tool to improve the competitiveness of these systems [ 46 ], which are otherwise at a disadvantage compared to permanently establishing intensive systems, both from an economic and productive point of view [ 47 ]. Areas with low cropping potential (e.g., arid or mountainous areas), such as the farms studied, depend on grazing [ 14 , 17 ]. While vegetation plays a critical role in mitigating climate change, it also plays an important role in supporting global biodiversity and providing many goods and services to humans [ 9 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, soil health and fertility and carbon sink ability by both soil and vegetation can be favored by properly managed ruminant grazing. In this sense, pasture-based carbon sequestration can mitigate, to varying degrees, the GHG emitted by the livestock it feeds as well [ 13 , 14 ]. Previous studies have shown that taking carbon sinks into account in the net GHG emission balance significantly reduces emissions per unit of product on farms with land-based grazing [ 6 , 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…An herbivory baseline that enteric herbivore emissions have been part of the natural uxes in the past and have a of inevitability future, because such emissions are consubstantial to the grazing ecological niche that dominates Open Ecosystems (Manzano and White 2019). Considering a signi cant fraction of herbivory as a natural process, as done in the present study, or in Pardo et al (2023) contrasts from the conventional approach of most studies. All livestock herbivory is usually considered as purely anthropic, and so are all enteric caused (e.g.…”
mentioning
confidence: 85%
“…But domestic grazing herbivores can indeed ful l ecological roles that are equivalent to wild herbivores, and their densities can also be equivalent (Manzano et al 2023a). At the same time, some authors have demanded that the consideration of baselines can be important in environmental assessment (Pardo et al 2023) and policymaking (Moncrieff et al 2016), for example, when supporting or limiting pastoralism (Manzano et al 2023a). In sum, new methodological approaches demand delving into a speci c framework for Open Ecosystems that explicitly includes and quanti es baseline values (Manzano and White 2019).…”
mentioning
confidence: 99%
“…We can help nuancing current calls to shift into plant-based diets to increase the sustainability of the food system 24 , because the resulting abandoned land will clearly not be a zero-emission scenario 8 . Instead, livestock systems that mimic natural migratory herbivore systems as much as possible, such as mobile pastoralism, should be promoted to mitigate climate change at the expense of industrialized high-input production systems 10,25 . In addition, decisions to promote wildlife conservation or pastoralism cannot rest by putative advantages to GHG emissions but must focus on other reasons or effects.…”
Section: Introductionmentioning
confidence: 99%